Understanding along-strike variability in controlling mechanisms of paleoenvironmental conditions and stratigraphic architecture: Ordovician successions in the Alborz Mountains of Iran at the northern Gondwana margin. (June 2022) - Bayet-Goll, Aram; Sharafi, Mahmoud; Jazimagh, Neda; Brandano, Marco
Abstract: Changes in stacking patterns of facies, stratal architecture and shoreline trajectory along depositional strike are mainly dependent on along-strike differences in factors such as physical processes (rivers, waves, tides), tectonics, eustatic changes, sediment supply, and local physiography. The lower-upper Ordovician successions (Lashkerak Formation) deposited in a Peri-Gondwana shallow continental shelf have been interpreted using the sequence stratigraphic concepts. This approach allowed to highlight main differences along-strike in the co-existing depositional systems (coastal plains, estuaries, deltas, and shoreline to shelf systems) in the Alborz basin along the northern edge of Gondwana. On the basis of sedimentary and ichnological characteristics, the siliciclastic successions are divided into four facies associations: (i) Wave-dominated estuarine, (ii) Wave-dominated shoreface-offshore complex, (iii) Mixed fluvial (F)- and wave (W)-influenced delta ( Fw and Wf ), and (iv) Tide-dominated, fluvial-influenced delta ( Tf ). Six third-order depositional sequences (DS1-DS6) were recognized, each of them are bounded by unconformities and pronounced shifts in the facies. Along depositional strike (NE/SW- a distance of c. 150 km), significant intrabasinal changes in sediment supply produced evident lateral changes in the shoreline trajectory and stratal architecture, of the DS1-DS3 (Tremadocian-Floian), may be attributed to differences in physical processes (rivers, waves, tides activity) and topographic irregularities derive probably by different rates of subsidence in the basin. During the deposition of the DS1-DS3, a significant along-strike differences in the composition of ichnological suites and the lifestyle of benthonic organisms, dependent on the relative supremacy of wave, storm, river, and tidal processes. Sedimentary supply and processes are the main controlling factors for the stratigraphic architecture rather than the tectonic activity between Tremadocian and Floian. While during the Darriwilian-Katian interval (DS4-DS6), the tectonic activity predominates with the beginning of extensional phases related to the rifting in the Alborz basin causing the activation of syn-depositional normal faults and the development of block-faulted craton-ward margin. Typically, differential subsidence due to extensional tectonic activity causes the uplift of tectonic blocks west of the Alborz Basin into the emerging areas, on one hand, and simultaneous deepening-upward stacking patterns (i.e., increased subsidence rates) in the hanging-wall depocenters of east of the Alborz Basin, on the other hand. This outcrop-based study suggests that the identification of genetically related depositional units in a larger paleogeographic context is fundamental for understanding along-strike variability in controlling mechanisms of the spatial distribution and stratigraphic architecture of coexisting and linked depositional systems. Highlights: Analyze along-strike variations in stratigraphic architecture of the Ordovician successions. Synthesis of autocyclic and allocyclic controls on changes in accommodation space along depositional strike. Interpreting along-strike variability in controlling mechanisms of stratigraphic architecture. Unravelling the palaeogeography of continental shelf of the Prototethys margin along the northern edge of Gondwana. Results are useful for correlation to Ordovician strata in other parts of Gondwana.